2020
DOI: 10.14414/jebav.v23i1.2153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Characteristics on Capital Structure in Indonesia

Abstract: This study aims to determine the effect of corporate characteristics on the company's capital structure, which plays a fundamental role in the proportion of debt and equity financing risks. The research method used is purposive sampling. This research's population is non-financial issuers listed on the Indonesia Stock Exchange with quarterly data for the period of 2010-2017. The analysis is performed using panel data with six independent variables and two control variables. The results of this study indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
3
11
0
2
Order By: Relevance
“…Lastly, the other factors that affect firm performance are firm size, leverage, and industry type (Kechi, 2011). Hence, ownership concentration is related to firm value since traditional theories argued that when ownership of a firm is concentrated in the hand of large shareholders, they have the incentive to monitor the managers' action through direct intervention to reduce agency problem (Chen & Swan, 2010;Albart et al, 2020). Also, in the studies of a diversification strategy, it was found that ownership concentration enhances corporate diversification and performance of a firm because it constitutes the largest investment in a corporate firm (Genc & Angelo 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the other factors that affect firm performance are firm size, leverage, and industry type (Kechi, 2011). Hence, ownership concentration is related to firm value since traditional theories argued that when ownership of a firm is concentrated in the hand of large shareholders, they have the incentive to monitor the managers' action through direct intervention to reduce agency problem (Chen & Swan, 2010;Albart et al, 2020). Also, in the studies of a diversification strategy, it was found that ownership concentration enhances corporate diversification and performance of a firm because it constitutes the largest investment in a corporate firm (Genc & Angelo 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The first hypothesis testing of this study refers to the research of Albart et al (2020), where the dependent variable used is leverage with a proxy debt to equity ratio (Total Debt / Total Equity). The first independent variable in the first hypothesis test is profitability which is calculated by Earnings Before Interest and Taxes (EBIT) / Total Assets.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the Growth variable is the third independent variable in the first hypothesis test that we use the growth of company assets over time. The use of proxies on each of the independent variables to test the first hypothesis is based on the research of Mihalca (2011), Nosita (2012), Surwanti (2015, Mawitjere (2016), andAlbart et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian terdahulu mengenai pengaruh ukuran perusahaan memiliki hasil yang beragam. Menurut Naser et al (2015); Gharaibeh (2015); Sumedrea (2015); Shah, Rashid, and Khaleequzzaman (2017); Akgul and Sigali (2018); Yildirim, Masih, and Bacha (2018); Iqbal, Ahmad, and Ali (2019); Albart et al (2020), bahwa ukuran perusahaan berpengaruh signifikan dan positif terhadap struktur modal. Sedangkan menurut Öztekin (2015); Wijayanti (2018) ukuran perusahaan hanya berpengaruh positif terhadap struktur modal.…”
Section: Telaah Literaturunclassified